Controversy as a Moderator of the Impact of Environmental, Social, and Governance (ESG) on Corporate Value - Siti Aisyah; Dian Widyantini; Victor Pattiasina; Maha Martabar Mangatas L; Musran Munizu (Dinasti Publisher, 2025)
This research examines the relationship between Environmental, Social, and Governance (ESG) and company value. In addition, this study also tested the involvement of ESG controversy as a moderating variable. The population in this study were all members of the IDX ESG Leader index (IDXESGL) and the companies used as samples were 150 companies during 5 years of observation. The sample in this study was determined using the proportional sampling method and obtained a sample of 70 companies. The research results show that environmental, social and governance (ESG) influences company value. Apart from that, there is a moderating influence of the controversial variable on the relationship between environmental, social and governance (ESG) on company value. The research data analysis was analyzed using SmartPLS software.